Model Dinamika Sistem Pengelolaan Hutan Lindung Berbasis Causal Loop Diagram - Widiastuty, Wiwid; Walukow, Auldry F.; Siallagan, Johnson; Manalu, Janviter; Warpur, Maklon (Jurnal Inovasi Global, 2026)
Protected forest management is a complex issue because it is influenced by the interaction of interrelated social, economic, and environmental factors. Sectoral approaches are often not able to explain the cause-and-effect relationship comprehensively, so a dynamic systems approach is needed. This research aims to analyze the management system of protected forests using a causal loop diagram (CLD) approach in Mamberamo Tengah Regency. The research employed a mixed-method approach, including questionnaires, interviews, and land cover change analysis. The results indicate that forest management is influenced by the interaction of social, economic, and environmental factors. Reinforcing loops are dominated by economic dependency and forest exploitation, leading to increased forest degradation. Meanwhile, balancing loops are formed through improved knowledge, awareness, and government support, which promote conservation and forest protection. Key leverage points include alternative economic development, community education, institutional strengthening, and control of external exploitation. The model highlights the importance of a system dynamics approach for sustainable forest management.